STRATEGI PENANGANAN TITIK RAWAN KECELAKAAN RUAS JALAN SP. PENYANDINGAN – PEMATANG PANGGANG JALUR LINTAS TIMUR SUMATERA SELATAN - Achmad Djunaidi (Jurnal Tekno Global, 2018)
Sp. Penyandingan – Pematang Panggang highway in thelastthreeyearshas arecord oftrafficaccidentsincreasedwiththe victim died. Based on the perception ofthe experts which were processedby the method ofAHP, humansare the main factorscausingaccidentswithfatalities(66.88%)., followed by the physical conditionof thesub-human factors (51.71%), geometrichorizontal(37.14%) of thesub-factor of the road, speed(60.27%) of thesub-factor of a vehicle.Withconditions of alinemenhorizontalandverticalalinemenandwitha highvolume oftraffic, theroadshaveaccident-points, from25based onsurveythe crash site,there are 5 critical points (black Spot)that need comprehensive treatment.. Based on AEK the black spot of this road are 1) Mulya Guna (Air Jernih) Km 97, 2) Muara Burnai 1 Km 105, 3) Muara Burnai 2 Km 112, 4) Tugu Jaya Km 125+4, 5)Tugu Mulya Km 136+1. The perception of experts in strategi of blackspots treatments, environment criteria is the main factor (28.63%), human (27.65%), roads (25.11%), vehicles (18:01%). Priorityalternativein strategy of blackspots treatmentsbased on the factorsthat influenced itare widening (31.40%), traffic hazard (26.69%), median(20.70%), harmonization ofroad signs andmarkings(20.61%)Keywords: blackspots, human, environment, widening.